Impact of ESG Performance on Financial Performance : Evidence from 141 Indian Companies - Bhavnani, Bhumika; Gola, K. R. (Prabandhan: Indian Journal of Management, 2026)
Purpose : This study analyzed the effect of environmental, social, and governance (ESG) performance and its individual components on the financial performance of Indian companies. Methodology : A sample of 141 Indian companies across various sectors was analyzed for the time period 2019–2024. On the basis of the Hausman test, this study used fixed effects panel regression to test the stated relationships. The study estimated the effect of one-year lagged ESG scores (Environmental score, social score, and governance score) on financial outcomes: Return on assets (ROA) and market-to-book (MTB) value. Findings : The results indicated that ESG performance negatively impacted short-term profitability and earnings, measured by ROA. However, it was positively correlated with market valuations, reflecting investor confidence in the long-term sustainability of these companies, measured by MTB. Practical Implications : The study drew policy implications with special reference to Indian policy instruments such as the Securities and Exchange Board of India’s ESG mutual fund regulations and tax-free issuance of green bonds. It is also recommended that the Government provide grants, awards, subsidies, or tax incentives to companies to encourage business sustainability. Originality : Most of the previous Indian studies focused on analyzing the effect of the overall ESG performance of the current period on financial performance. In contrast, this study investigated the effect of one-year lagged ESG performance and its individual components (E, S, and G) on financial outcomes.